Mast Cells Promote Inflammatory Th17 Cells and Impair Treg Cells Through an IL-1β and PGE2 Axis - Leveque E; Joulia R; Battut L; Laurent C; Valitutti S; Cénac N; Dietrich G; Espinosa E (Journal of Inflammation Research)
Edouard Leveque,1,2 Régis Joulia,3 Louise Battut,2,4 Camille Laurent,1,2,5 Salvatore Valitutti,1,2,5 Nicolas Cénac,2,4 Gilles Dietrich,2,4 Eric Espinosa2,4 1Centre de Recherche en Cancérologie de Toulouse (CRCT), INSERM UMR1037, CNRS UMR5071, Toulouse, F-31000, France; 2Université Toulouse III Paul Sabatier, Toulouse, F-31062, France; 3National Heart and Lung Institute, Imperial College London, London, SW7 2AZ, UK; 4Institut de Recherche en Santé Digestive (IRSD), INSERM U1220, INRA, INP-ENVT, Toulouse, F-31024, France; 5CHU Toulouse, Department of Pathology, Institut Universitaire du Cancer - Oncopole de Toulouse, Toulouse, F-31000, FranceCorrespondence: Eric Espinosa, INSERM U1220, Institut de Recherche en Santé Digestive (IRSD), CHU Purpan, Place du Dr Baylac, CS 60039, Toulouse Cedex 3, 31024, France, Email eric.espinosa@inserm.frPurpose: CD4+ effector T cells (Teffs) play a key role in immune responses by infiltrating the sites of inflammation and modulating local leukocyte activity. In turn resident immune cells shape their response. This study aimed to investigate the influence of mast cells (MCs) on Teff biological responses.Methods: This study examined human MC-Teff interactions, focusing on how MCs shape Teff responses. Flow cytometry, qRT-PCR, and cytokine assays were used to analyze the impact of primary human MCs on the Teff phenotype and function. MC-Teff crosstalk within Crohn’s disease patient tissues was assessed using confocal microscopy and advanced image analysis.Results: MCs promoted the differentiation of Th17 cells, particularly the inflammatory Th17.1 subset, that secretes IFN-γ and GM-CSF. This differentiation was driven by the PGE2 and IL-1β axis. Additionally, MCs disrupted the phenotype and impaired the suppressive function of regulatory T cells (Tregs) through PGE2, skewing the Th17/Treg balance. The analysis of biopsies from patients with Crohn’s disease indicated that this MC/Teff crosstalk may play a role in the pathogenesis of auto-inflammatory processes.Conclusion: MCs influence CD4+ T cell responses by fostering pro-inflammatory Th17 differentiation while impairing Treg function. This interaction underpins a Th17/Treg imbalance, which is significant in auto-inflammatory diseases such as Crohn’s disease, positioning MCs as critical drivers of disease pathogenesis.Plain language summary: The immune system functions through complex interactions between different types of cells to protect the body from harm. CD4+ T cells are crucial in managing inflammation by directing other immune cells. Mast cells, found in tissues such as the skin and gut, are among the first to respond to potential threats and can influence T cell behavior. This study examined how mast cells and T cells interact in vitro, particularly in Crohn’s disease, a condition in which the immune system causes gut inflammation.We used laboratory techniques to study how mast cells affect T cells, examining their behavior and communication. We also studied tissue samples from individuals with Crohn’s to determine how these interactions occur in real life.We found that mast cells encourage the development of inflammatory T cells called Th17, particularly a type known as Th17.1, which produce strong inflammatory signals. This process relies on specific molecules such as PGE2 and IL-1β. Simultaneously, mast cells weaken the function of regulatory T cells (Tregs), which normally help control inflammation. This leads to an imbalance between Th17 cells and Tregs, tipping the immune system toward excessive inflammation. In tissue samples from Crohn’s disease patients, we found evidence of this imbalance, suggesting that mast cells play a major role in driving harmful inflammation.These findings help us understand why inflammation becomes uncontrollable in diseases such as Crohn’s disease. They also suggest that targeting mast cells could be a promising strategy for new treatments.Keywords: mast cells, helper T cells, prostaglandin E2, IL-1β, Th17, inflammatory Th17.1 cells, Crohn disease, IL-17, IFN-&#x03B3